Parody Facebook Accounts as Facilitators of Fake News: Perceptions of South Africa - Modiba, Tumelo Matome (Innovation Journal of Social Sciences and Economic Review, 2024)
The purpose of this study was to examine the use of Facebook as a platform for reporting fake news. Researchers investigated the following problem: Facebook users tend to disseminate fake news, adversely affecting the credibility of content posted on Facebook as factual information. Facebook is misused by individuals who post fake news fabricated to degrade the integrity and credibility of others. However, organizations and other community groups are also drawn to the platform because it connects them to the public in valuable ways. This occurs as participation increases and the amount of data generated improves the platform's ability to advise, recommend, and share information among all parties. Therefore, the study was underpinned by practice theories. An exploratory research design was implemented to provide a strong and robust connection between a cause and an outcome. This exploration represents how Facebook users tend to use this platform to address social problems and their attitudes toward each other, as it was originally meant for socialization, entertainment, and education. Hence, the need to inquire about the use of Facebook for fake news was qualitatively researched. For the data collection process, semi-structured interviews were conducted with Facebook users. Thematic analysis was used to analyze the data and develop themes. The key conclusion of the study is that there has been an increase in the quantity of fake news on Facebook across the country. This study aims to theoretically contribute to the existing body of knowledge in media and communication studies. It indicates that in the future, researchers will discover current knowledge regarding parody Facebook profiles as facilitators of fake news perceptions from Polokwane Municipality, Limpopo South, in the field of media and communication studies.
Keywords: Parody; Facebook; Fake news; Perception and Facilitator Fake News; Social Media; Media Credibility; Online Misinformation